Investigation of Al2O3 Nanofluid Viscosity for Different Water/EG Mixture Based. (November 2015) - Hamid, K. Abdul; Azmi, W.H.; Mamat, Rizalman; Usri, N.A.; Najafi, G.
Abstract: Viscosity of Al2 O3 nanoparticle dispersed in mixture of water and ethylene glycol (EG) were investigated experimentally. The effect of based fluid ratio (water:EG) to nanofluid viscosity was investigated. Nanofluids with volume concentration up to 2.0% were prepared with 13 nm Al2 O3 nanoparticles for viscosity measurement. Two-step methods were used in preparation of Al2 O3 nanoparticles. The nanoparticles were suspended in three different ratios of water:EG which are 40:60, 50:50 and 60:40 by volume percent. The measurements of viscosity were performed using Brookfield LVDV III Ultra Rheometer for nanofluid temperature of 30 to 70 ̊C. Viscosity of nanofluid was observed to be influenced by nanofluid concentration, temperature and ethylene glycol concentration in the base fluid.